How Does the Analytical Quality of the High-Sensitivity Cardiac Troponin T Assay Affect the ESC Rule Out Algorithm for NSTEMI? - Haagensen, Kristin; Collinson, Paul; Åsberg, Arne; Aakre, Kristin M (Clinical chemistry (Baltimore, Md.), 2019)
The ESC algorithm requires that a difference of <3 ng/L can be detected (4) and, by implication, that there is an absolute RCV (8) value of <3 ng/L. Because cardiac troponin is reported in whole numbers, the actual lowest detectable 8 value should be 2 ng/L. [...]the hs-cTnT assay showed satisfactory analytical precision when using 2 Cobas e801 modules, but laboratories should still verify their CVA locally before implementing the ESC rule-out algorithm. Hormone Laboratory Haukeland University Hospital PO Box 1400 5021 Bergen, Norway E-mail kristin.moberg.aakre@helse-bergen.no Previously published online at DOI: 10.1373/clinchem.2018.298703 1 Nonstandard abbreviations: ESC, European Society of Cardiology; NSTEMI, non-ST elevation myocardial infarction; hs-cTnT, high-sensitivity cardiac troponin T; CVA, analytical variation; RCV, reference change values; CV,, intra-individual biological variation.